Participation in medical research as a resource‐seeking strategy in socio‐economically vulnerable communities: call for research and action. Issue 1 (10th October 2014) - Ravinetto, Raffaella M.; Afolabi, Muhammed O.; Okebe, Joseph; Van Nuil, Jennifer Ilo; Lutumba, Pascal; Mavoko, Hypolite Muhindo; Nahum, Alain; Tinto, Halidou; Addissie, Adamu; D'Alessandro, Umberto; Grietens, Koen Peeters
Abstract The freedom to consent to participate in medical research is a complex subject, particularly in socio‐economically vulnerable communities, where numerous factors may limit the efficacy of the informed consent process. Informal consultation among members of the Switching the Poles Clinical Research Network coming from various sub‐Saharan African countries, that is Burkina Faso, The Gambia, Rwanda, Ethiopia, the Democratic Republic of Congo (DRC) and Benin, seems to support the hypothesis that in socio‐economical vulnerable communities with inadequate access to health care, the decision to participate in research is often taken irrespectively of the contents of the informed consent interview, and it is largely driven by the opportunity to access free or better quality care and other indirect benefits. Populations' vulnerability due to poverty and/or social exclusion should obviously not lead to exclusion from medical research, which is most often crucially needed to address their health problems. Nonetheless, to reduce the possibility of exploitation, there is the need to further investigate the complex links between socio‐economical vulnerability, access to health care and individual freedom to decide on participation in medical research. This needs bringing together clinical researchers, social scientists and bioethicists in transdisciplinary collaborative research efforts that require the collective input from researchers, research sponsors and funders.